Max Weber Never Was Mainstream—But Who Made Him a Classic of Sociology? - Kaesler, Dirk (Serendipities. Journal for the Sociology and History of the Social Sciences, 2016)
If by “mainstream sociology” one understands a specific paradigm that dominates the discourses of sociology because its adherents form the majority of the discipline, then Max Weber’s program of a sociology that is built upon “interpretative understanding of social action and thereby with a causal explanation of its course and consequences,” was never mainstream, not during his lifetime (1864–1920) or since. So why has he become this overpowering “classic” of sociology? Who is responsible for this development? This paper does not aim to reconstruct the entire impact of Max Weber upon the history and presence of sociology since his death. Starting with the observation that he has been made into an indisputable “classic” of international sociology this paper, first aims to depict the sharp contrast between the weak and very selective impact and reception of Weber's work during his lifetime and its significance for international sociology today. Second, it attempts to explain Weber's career as a classic of sociology, having become—along with Marx and Durkheim—one of the pillars of a “Holy Trinity” in international sociology. Thirdly, after offering a general overview of forty-three individuals who may be regarded as mainly responsible for the fashioning of the sociological classic Max Weber, it concentrates upon the three most important figures by sketching their quite distinct ideas, interests and roles in this endeavor.